An innovative numerical modeling strategy for the structural analysis of historical monumental buildings. (1st February 2017) - Castellazzi, Giovanni; D'Altri, Antonio Maria; de Miranda, Stefano; Ubertini, Francesco
Highlights: A new modeling strategy for structural analysis of historical monumental buildings is presented. Semi-automatic transformation of points cloud surveyed produces the finite element mesh. Validation of the new strategy is performed on the San Felice sul Panaro (Italy) fortress. The comparison between the simulated and the real crack pattern shows a good agreement. Abstract: In this paper, an innovative numerical modeling strategy for the structural analysis of historical monumental buildings is presented. The strategy is based on a procedure that enables the semi-automatic transformation of a three-dimensional points cloud surveyed through terrestrial laser scanner or closed range photogrammetry into a three-dimensional finite element mesh, as well as its mechanical characterization. Therefore, an increase of the level of automation in the mesh generation process is attained and a large reduction in the required time in comparison with traditional modeling procedures is achieved. In order to validate the new strategy, an application to the case study of the San Felice sul Panaro (Italy) fortress is carried out. The reliability of the proposed model is assessed through a comparison between the results of structural analyses and the crack pattern experienced by the structure during the Emilia earthquake (2012). Moreover, the vulnerability assessment of the main tower of the fortress is performed through simplified pushover analyses conducted on the generated mesh.